The Criminal Liability of Political Parties for Corruption Offenses Committed by Their Members - Jiwanti, Ainun; Setiawan, Wiranto Tri (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The inadequacy of existing regulations governing the criminal liability of political parties for corruption offenses committed by their members, despite the fact that, conceptually, political parties may be classified as corporate entities. It aims to analyze the construction of criminal liability applicable to political parties and to develop an ideal model for future regulation. This research employs a normative legal method, utilizing statutory, conceptual, and case-based approaches. The findings reveal that political parties may be held criminally liable when they benefit from, tolerate, or fail to prevent criminal conduct. However, the current positive legal framework remains ambiguous and fragmented. Accordingly, a reformulation is required through the integration of corporate liability principles and contemporary criminal law theory. The study concludes that strengthening the regulatory framework is essential to enhance the effectiveness of law enforcement and the prevention of corruption within a democratic system.